Familial, autosomal dominant chronic muco-cutaneous candidiasis. - Garofalo, L. (European Journal of Pediatric Dermatology, 2016)
Chronic muco-cutaneous candidiasis (CMCC) is a rare disease characterized by chronic recurrent infections mainly caused by Candida albicans; the infections affecting the mucous membranes, nails and skin, do not give systemic manifestations, have varying severity, and may be associated or not to other problems. CCMC may be classified (1) in familial hereditary forms and non familial forms. Hereditary forms can be transmitted with an autosomal dominant or autosomal recessive trait and associated or not to endocrinopathy. Among the familial forms were also described an autosomal dominant subtype with intercellular adhesion molecule deficit (ICAM-1) and an autosomal recessive subtype with HyperIgE. The genetic basis for autosomal dominant forms was identified in mutations of STAT1 (signal transducer and activator transcription 1); the latter through a reduced Th1 and Th17 response would lead to a lack of defense against fungal infections (3). A defective IL-17 response was also demonstrated in autosomal recessive forms of CMCC (2). The severity of the autosomal dominant forms not associated with polyendocrinopathy or other immune deficiencies is highly variable; often these forms are compatible with an almost normal life. The sensitivity to therapy is also variable: besides forms that rapidly recur after the suspension of oral imidazoles there are forms that after the first cycle of antimycotics remain silent for years.